Applying Tools From Human-Centered Design to Social Marketing Planning - Biroscak, Brian J.; Schneider, Tali; Martinez Tyson, Dinorah; Aguado Loi, Claudia X.; Bryant, Carol A. (Social marketing quarterly, 2018)
In this “Tools From the Field” paper, we report our experiences using human-centered design (HCD), a process for using innovation as a means of developing more effective marketing offerings. The context for our use of HCD tools was a partnership with a new community committee. We combined elements of our previous social marketing frameworks -Community-Based Prevention Marketing (CBPM) for Program Development; CBPM for Policy Development–into a version better suited to address complex, dynamic problems that require a whole-systems perspective. Our product development work for this next iteration of the CBPM framework incorporated several HCD tools adapted from the prolific design firm, IDEO. The HCD process consists of three phases: inspiration (e.g., learning from those that one is designing for), ideation (e.g., brainstorming and prototyping), and implementation (e.g., building partnerships and launching a business model). In this paper, we describe “tools” for the application of HCD within the context of rapidly prototyping and testing CBPM framework activities for use with our community committee partners; we provide practical advice for the use of these tools (“process points”); and we present a real-world application from development of our new CBPM framework (“tools in action”). Overall, the HCD tools from IDEO helped us see new opportunities for our framework, transform insights into actionable ideas, and increase the speed of producing a minimum viable product and gathering feedback on it from our customers. We believe that HCD tools are worth exploring when it comes to the social marketing planning process.